Blastic Plasmacytoid Dendritic Cell Neoplasm: A Rapidly Progressive and Fatal Disease without Aggressive Intervention. Issue 6 (January 2013) - Prochaska, Lindsey; Dakhil, Christopher; Mathur, Sharad
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an aggressive myeloid neoplasm derived from plasmacytoid monocytes. The most common presentation involves cutaneous manifestations, which are often accompanied by bone marrow involvement. The tumor cells reveal an immature blastic appearance and diagnosis is based on the expression of cluster of differentiation (CD)4 and CD56. The literature reports a high relapse rate and poor prognosis when treated with leukemia-type induction chemotherapy alone; however, long-term remission is attainable with allogeneic stem cell transplantation in the first complete remission. Here, we report the dismal course of a patient with BPDCN with cutaneous and bone marrow involvement unable to undergo an aggressive intervention.